Study on the durability of compression behavior for glass fiber‐reinforced polypropylene thermoplastic composite bars in various aging environments - Zhou, Ping; Dong, Shaoce; Li, Chenggao; Kong, Deao; Bai, Yanbo; Xian, Guijun; Yue, Qingrui (Polymer composites, 2024)
In reinforced concrete structures, GFRP bars are becoming acceptable as internal reinforcement subject to compressive load and hygrothermal environments. The paper presents an experimental study on the compressive behavior, thermodynamic properties, and degradation mechanism of the glass fiber‐reinforced polypropylene (GFRPP) bars after aging in distilled water (DW), alkaline solution (AS) and seawater and sea sand concrete (SWSSC) solution at 21, 40, and 60°C up to 120 days. The effect of specimen assembly methods, and slenderness rations (Lu/Db) on the compressive behavior was evaluated on the control GFRPP bars. After immersion, the compressive strength of the GFRPP bars was significantly affected by the type of solution, immersion time, and temperature. Typically, the compressive strength retention was decreased by 25.8%, 30.0%, and 33.0% at 60°C in DW, AS, and SWSSC solutions, respectively. The degradation mechanism of the compressive behavior of GFRPP bars was revealed through SEM images and FTIR spectroscopy analysis, and the debonding of fiber‐resin interfaces, chemical etching of glass fibers, and changes in polypropylene functional groups were confirmed or discovered. Finally, based on the Arrhenius theory, the long‐term life prediction of compression strength in three typical service environments was conducted to provide the design guideline for reinforcement concrete. Highlights Effect of specimen assembly and Lu/db on compressive behavior of GFRPP bars Thermodynamic behavior of the GFRPP bars under different aging environments Revealed the degradation mechanism of GFRPP bars under hygrothermal environments Predicted the service life of GFRPP bars in typical service environments Research method and route of compressive durability of GFRPP bar.